The ohlin-heckscher theory of the basis and effects of commodity trade - Ford J. L (London : Asia publishing house, 1965)
This book examines the Ohlin-heckscher theory of trade, to ascertain the effectiveness of the theory on commodity market.
asm; 28/02/19
Loans
Keywords: Commerce; Heckscher-Ohlin principle